The influences of restaurant service quality and ambience towards customer satisfaction - Maulana, Moehamad Irwan; Sugandi, Gagan; Razak, Anis Abd (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this paper is to measure the relationship between service quality and ambience in restaurants towards customer satisfaction. Food business have been growing rapidly recently. More and more new restaurants with various cousins and attractions in order to capture the customer to dine in. The increase number of tourist domestic and internationally make prosper the industry competition. Data were collected using questionnaire distributed among the restaurant visitors. 270 questionnaires distributed but only 212 returns completely. The results indicate that both service quality and ambience is equally important in restaurant industry towards customer satisfaction. Service provider must learn the current market trends and preferences as there is a change in customer behaviour lead to purchase intentions. Customer is getting sophisticated and the competition create advantage to the customer in selecting the service provider that can meet their needs and wants.